Marx barks - Bru, Sascha (Primerjalna književnost, 2006)
How do literary agency (that is, the intentionally acting "subject", whether an individual, group or class) and social structures (i.e. theoretical models devised to objectify the interfaces between agents) relate? Exploring the work of Köhler, Bürger, Dubois and Bourdieu, the essay shows how valuable "social structures" have been developed in literary theory. Bringing these up to speed with the post-Marxist and post-structuralist theory of Ernesto Laclau and Chantal Mouffe, the authors argue how a more balanced approach is also able to draw agency to the fore as a source of innovation and structural change. Italian Futurism provides a case in point.
Keywords: Laclau, Ernesto; Mouffe, Chantal, 1943-; literarna teorija; literary theory; sociologija literature; postmarksizem; futurizem